Hemodynamic effects of long-term morphological changes in the human carotid sinus. Issue 6 (13th April 2015) - Seong, Jaehoon; Jeong, Woowon; Smith, Nataliya; Towner, Rheal A.
Abstract Previous investigations of morphology for human carotid artery bifurcation from infancy to young adulthood found substantial growth of the internal carotid artery with advancing age, and the development of the carotid sinus at the root of the internal carotid artery during teenage years. Although the reasons for the appearance of the carotid sinus are not clearly understood yet, it has been hypothesized that the dilation of the carotid sinus serves to support pressure sensing, and slows the blood flow to reduce pulsatility to protect the brain. In order to understand this interesting evolvement at the carotid bifurcation in the aspects of fluid mechanics, we performed in vitro phase-contrast MR flow experiments using compliant silicone replicas of age-dependent carotid artery bifurcations. The silicone models in childhood, adolescence, and adulthood were fabricated using a rapid prototyping technique, and incorporated with a bench-top flow mock circulation loop using a computer-controlled piston pump. The results of the in vitro flow study showed highly complex flow characteristics at the bifurcation in all age-dependent models. However, the highest magnitude of kinetic energy was found at the internal carotid artery in the child model. The high kinetic energy in the internal carotid artery during childhood might be one of the local hemodynamic forces that initiate morphological long-term development of the carotid sinus in the human carotid bifurcation.